Analisis Potensi Penerimaan Retribusi Parkir di Kota Kupang - Frits O Fanggidae; Charles Kapioru (Jurnal Inovasi Kebijakan, 2016)
The total parking capacity of dynamic and static two-wheeled vehicles and four wheels at all points on-street parking and off-street parking in the city of Kupang is still very large. With the two-wheeler parking tariff is Rp . 2000 and a four-wheel Rp . 3000 , every year, the potential parking fees reached Rp . 7.603.200.000.- Given the number of vehicles continues to increase, it is necessary to implement appropriate control strategies for managing parking on-street and off-street, especially on collector roads, creating traffic regularity. In addition, the mechanisms and procedures for the collection of parking charges need improvement. Governments need to work with a person or board who has been licensed parking management through a tender system, with the results pattern of distribution following: 35% of parking management, parking attendants 25 % and government 40 %.